2017
DOI: 10.1177/1071100717738748
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Perioperative Complications of Outpatient Total Ankle Arthroplasty

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The patient was treated with I&D and intravenous antibiotics and the patient retained all components. Similarly, Borenstein et al 3 reported 1 ankle among 65 consecutive TAAs (1.5%) that experienced deep infection. The patient was treated with I&D and 6 weeks of intravenous antibiotics.…”
Section: Rationalementioning
confidence: 85%
“…The patient was treated with I&D and intravenous antibiotics and the patient retained all components. Similarly, Borenstein et al 3 reported 1 ankle among 65 consecutive TAAs (1.5%) that experienced deep infection. The patient was treated with I&D and 6 weeks of intravenous antibiotics.…”
Section: Rationalementioning
confidence: 85%
“…These complications included one (1.5%) minor wound dehiscence, one (1.5%) wound infection, two (3%) revision surgeries, and eight (12%) non-revision surgeries. This study demonstrated that outpatient TAA is a safe and beneficial choice in appropriately selected patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the safety and reduced costs of common orthopedic surgeries, including primary shoulder arthroplasty, hip arthroplasty, and knee arthroplasty, performed in the outpatient setting in selected patients [5-7]. Furthermore, there is evidence supporting the safety of outpatient total ankle arthroplasty and surgery for closed ankle fractures [8-10]. Although the literature shows promising trends of safety in areas of outpatient orthopedic surgeries, it lacks any large database studies evaluating common elective foot and ankle surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Although shorter hospital stays have been investigated for hip and knee arthroplasty, the same cannot be said for TAA, which presents its own unique challenges. Three separate studies have described outpatient TAA with excellent short-term outcomes and minimal complications [ 20 22 ]. However, these studies all shared the limitation of a small sample size ( N < 100), making it difficult to quantify short-term outcomes, particularly rare complications.…”
Section: Introductionmentioning
confidence: 99%